Pulmonary function, CT and echocardiographic abnormalities in sickle cell disease. Issue 8 (28th March 2014) - Lunt, Alan; Desai, Sujal R; Wells, Athol U; Hansell, David M; Mushemi, Sitali; Melikian, Narbeh; Shah, Ajay M; Thein, Swee Lay; Greenough, Anne
Abstract : Objectives: To test the hypothesis that vascular abnormalities on high-resolution CT (HRCT) would be associated with echocardiographic changes and lung function abnormalities in patients with sickle cell disease (SCD) and the decline in lung function seen in SCD patients. Methods: HRCT, echocardiography and lung function assessments were made in 35 adults, 20 of whom had previously been assessed a median of 6.6 years prior to this study. The pulmonary arterial dimensions on HRCT were quantified as the mean segmental pulmonary artery/bronchus (A/B) ratio and the summated cross-sectional area of all pulmonary vessels <5 mm in diameter (cross-sectional area (CSA)<5 mm%). Results: The segmental A/B ratio was negatively correlated with FEV1, vital capacity (VC), forced expiratory flow between 25% and 75% of VC (FEF25/75 ) and arterial oxygen saturation (SpO2 ) and positively with the residual volume: total lung capacity ratio (RV:TLC) and respiratory system resistance (Rrs). CSA<5 mm% was negatively correlated with FEV1, FEF25/75 and SpO2 and positively with RV, RV:TLC and respiratory system resistance (Rrs). There were significant correlations between cardiac output assessed by echocardiography and the segmental A/B ratio and CSA<5 mm%. Lung function (FEV1 p=0.0004, VC p=0.0347, FEF25/75 p=0.0033) and the segmental A/B ratio (p=0.0347) and CSA<5 mm% (p<0.0001) significantly deteriorated over the follow-up period. Conclusions: Abnormalities in pulmonary vascular volumes may explain some of the lung function abnormalities and the decline in lung function seen in adults with SCD.